HOW RICE SEED FARMERS PARTICIPATE IN ADDITIONAL PARTNERSHIP PROGRAM: EXPERIENCE FROM ACEH-INDONESIA - Setia Budi; Jamilah; Eva Wardah (RADJA PUBLIKA, 2023)
This study aims to determine the level of farmer participation in the agricultural extension partnership program in North Aceh and Pidie Jaya districts, Aceh-Indonesia. This is a case study involving 187 rice seed farmers as research samples. Data was measured and analyzed using a Likert Scale. The results showed that the level of farmer participation in the agricultural extension partnership program was good with an index value of 79.16%. Sequentially the response of farmers' involvement in agricultural activities (87.37%), provision of production facilities (84.24%) and program planning (80.14) were in very good category. The involvement of farmers in product processing (76.26%), program evaluation (74.69%) and product marketing (72.24%) is included in the good category.